Zero tillage potato cultivation an innovative technology for coastal saline soils - Sarangi, Sukanta K; Maji, B; Digar, S; Mahanta, K K; Sharma, P C; Mainuddin, M (Indian Farming, 2018)
Zero tillage potato cultivation is a promising technology for cropping system intensification in the rainfed low lands in coastal saline region, with limited use of irrigation water, less labour input and higher yield. This technology also resulted in higher net return and BCR compared to the conventional ridge and furrow method of potato cultivation. With adoption of this technology, there is increase in cropping intensity to 300%, better use of carry over soil moisture and rice crop residue. Therefore, this is a sustainable technology, which improve the livelihood of farming communities in coastal region of India.